2012
DOI: 10.5539/ijel.v2n6p91
|View full text |Cite
|
Sign up to set email alerts
|

Developing Speaking Skills through Reading

Abstract: There is an increasingly high relationship between reading and speaking skills. There is no question that people who develop large reading vocabularies tend to develop large speaking vocabularies. Indeed, reading power relies on continuous improvement in vocabulary knowledge that provides communication. The importance of word knowledge, which facilitates speaking skills, has been a major resource in the development of reading skills. Therefore fostering improvement in word knowledge through wide reading has th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 16 publications
7
56
0
7
Order By: Relevance
“…What the students have done showed that they were also able to communicate in English, although all the components were not optimal. Interestingly, the finding of the study also in line with Suprijono (2011), who found that using Make-A-Match technique in the learning process will make the students more interested and enthusiastic in the learning process and the teacher in the classroom (Jeremy Harmer, 2003;Mart, 2012;Nation & Newton, 2008;Rayhan, 2014).…”
Section: Discussionsupporting
confidence: 78%
“…What the students have done showed that they were also able to communicate in English, although all the components were not optimal. Interestingly, the finding of the study also in line with Suprijono (2011), who found that using Make-A-Match technique in the learning process will make the students more interested and enthusiastic in the learning process and the teacher in the classroom (Jeremy Harmer, 2003;Mart, 2012;Nation & Newton, 2008;Rayhan, 2014).…”
Section: Discussionsupporting
confidence: 78%
“…In addition, critical literacy and language skills development can be positively integrated (Huang, 2011). It is further demonstrated that fostering improvement in word knowledge through wide reading is potential for fostering the improvement in speaking skills (Mart, 2012). From the above mentioned empirical proofs, it can be sum up that text is then considered powerful for the EFL adult learners to improve their language skills, vocabulary, and grammar competence.…”
Section: Nurhayati 2012)mentioning
confidence: 95%
“…Epistemologically, reading has clear impact on the acquisition of other language skills; EFL writing is improved or should be improved through exposing learners to extensive reading (Kirin, 2010;Muslim, 2014;Mermelstein, 2015;Al-Mansour and Al-Shorman, 2014). In the same vein, research studies also reveal that talking books enhance EFL learner's speaking and pronunciation skills at different levels (Saka, 2015;Mart, 2012;Hamada, 2017;Hall, 2016).…”
Section: Introductionmentioning
confidence: 90%
“…Using such tools can potentially enhance language skills in general and improve reading skills in particular (Saka, 2015;Zolfagharkhani & Kowsary, 2013;Stroh, 2012;Seo, 2014;Al-Ma'shy, 2011;Mart, 2012;Kaderavek & Justice, 2002). In addition, read-aloud tools and talking story books are a source of vicarious entertainment for EFL young learners that make the class more enthralling and help them retain the components for longer time (Haven, 2000;Alna, 1999;Mallan, 1997;Cohen & Cowen, 2009).…”
Section: Significance Of the Studymentioning
confidence: 99%